[Gdańsk - Wrzeszcz, wille przy Alei Zwycięstwa] [aut. odb. Karol Nowaliński]. - Nowaliński, Karol (1935- ). (Karol Nowaliński, 1986)
Przedstawia wille obecnie nr 37-33 przy Alei Zwycięstwa (Halbe Allee), ok. 1910 r.